Place of behavior analysis in the changing culture of replication and statistical reporting in psychological science. Issue 1 (2nd January 2018) - Imam, Abdulrazaq A.
ABSTRACT: The "new" psychological science seeks to promote a culture of replication in response to rampant publication bias and some controversial failures to replicate. Two of the solutions adopted are the emphases on the New Statistics by Psychological Science and the growing use of replication repositories. Where does behavior analytic research fit in this effort? Although experimental and applied research methods in behavior analysis naturally are replication focused and replication friendly, trending growth in group designs in different areas of behavior analytic research suggests that we should be sharing the concerns in the broader psychological science community. What measures, if any, are behavior analytic journals taking or should be taking to address these concerns? Not all of the solutions under consideration in the "new" psychological science are amenable to behavior analytic research. How do we proceed? Recommendations include formulating editorial policies in behavior analytic journals and organizational programming collaborations, for example, between Association for Behavior Analysis International and the Association for Psychological Science.